2015
DOI: 10.1189/jlb.4a0714-356r
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine modulates HIV-1 integration in primary CD4+ T cells: implications in HIV-1 pathogenesis in drug-abusing patients

Abstract: Epidemiologic studies suggest that cocaine abuse worsens HIV-1 disease progression. Increased viral load has been suggested to play a key role for the accelerated HIV disease among cocaine-abusing patients. The goal of this study was to investigate whether cocaine enhances proviral DNA integration as a mechanism to increase viral load. We infected CD4(+) T cells that are the primary targets of HIV-1 in vivo and treated the cells with physiologically relevant concentrations of cocaine (1 µM-100 µM). Proviral DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 71 publications
(149 reference statements)
1
28
0
Order By: Relevance
“…4), or resulted in a dramatic alteration in the formation of viral DNA ends (Tables 1 and 2). To test this hypothesis, we prepared cytoplasmic extracts containing PICs (Cy-PICs) from SupT1 cells acutely infected with a high concentration (ϳ1500 ng of p24 equivalent) of DNase I-treated HIV-1 particles (72,73,76). These PICs were subjected to integration assay in vitro, and viral DNA integration was quantified by nested qPCR (76,77).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4), or resulted in a dramatic alteration in the formation of viral DNA ends (Tables 1 and 2). To test this hypothesis, we prepared cytoplasmic extracts containing PICs (Cy-PICs) from SupT1 cells acutely infected with a high concentration (ϳ1500 ng of p24 equivalent) of DNase I-treated HIV-1 particles (72,73,76). These PICs were subjected to integration assay in vitro, and viral DNA integration was quantified by nested qPCR (76,77).…”
Section: Resultsmentioning
confidence: 99%
“…SupT1 cells were inoculated with high-titer HIV-1 particles (1,500 ng/ml of p24), and PIC-containing cytoplasmic extracts (Cy-PICs) were isolated from these cells. In vitro integration assays using the Cy-PICs as the source of integration activity and quantification of viral DNA integration by nested qPCR were carried out as described previously(76,77).Several controls were included in parallel to ascertain the specificity of the PIC-associated integration activity. (B) Integration activity with different amounts of PICs.…”
mentioning
confidence: 99%
“…Risky behavior associated with cocaine increases the probability of acquiring HIV and undermines adherence to treatment1234567. However, independent of behavioral factors, studies indicate enhanced replication and transmission of HIV-1 among cocaine using HIV-1 infected individuals489101112131415161718.…”
Section: Discussionmentioning
confidence: 99%
“…Cocaine is a commonly used illicit drug and prominently linked to HIV-1 infection and spread by both fostering high risk behaviors and facilitating the pathobiology of the virus1234567. Prior studies have shown that cocaine enhances viral replication in various cell types and alters the immune response by regulating the secretion of cytokines and expression of their receptors, accelerating the decline of CD4+ T-cells and disrupting the integrity of the blood-brain barrier489101112131415161718. However, the molecular mechanisms whereby cocaine may act as a cofactor for HIV-1 pathogenesis are not fully defined.…”
mentioning
confidence: 99%
“…This method utilizes a nested qPCR-based strategy for measuring PIC-associated IVI activity, and the procedures are adapted, with modifications, from protocols published by the Engelman laboratory 19,20,21 . In this method, the PIC-associated integration activity is initiated by providing a heterologous linear target DNA 21 , and the DNA products resulting from this integration reaction are purified and used as the starting material for subsequent PCR-based quantification. In the first-round conventional PCR, the viral-target DNA junctions are amplified using appropriate primers.…”
Section: In Vitro Integration Activity Of Hiv-1 Picsmentioning
confidence: 99%